The Effect of Touching Cones Training on The Reaction Speed of Futsal Goalkeepers - Febrian, Akhmad; Lestari, Hikmah; Hermansah, Bambang (Universitas PGRI Palembang, 2025)
This study aims to determine the effect of touching cones training on the reaction speed of futsal goalkeepers at SMA PGRI 2 Palembang. The research method used was experimental with a one-group pretest-posttest design involving 6 active goalkeepers. The training program was conducted over 16 sessions, with a frequency of 4 times per week and a duration of 120 minutes per session. The instrument used was a visual reaction test measured using a digital stopwatch. The pretest results showed an average reaction time of 0.385 seconds, while the posttest results improved to an average of 0.22 seconds. The Shapiro-Wilk normality test indicated that the data were normally distributed (p > 0.05). The hypothesis test using the t-test resulted in a t-value (tcount) of 17.23369 and a t-table value (ttable) of 2.571 at a 5% significance level, meaning tcount > ttable, so the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This indicates a significant effect of touching cones training on improving the reaction speed of futsal goalkeepers. The training has proven effective in enhancing visual response speed to stimuli, which is crucial for goalkeeper performance. This research may serve as a reference for coaches in designing reaction-based training programs for futsal goalkeepers.